Teachers’ Perspectives on the Implementation Process of the Century of Türkiye Education Model. - Şener, Gönül (Electronic Turkish Studies)
Century of Türkiye Education Model (CTEM), developed by the Ministry of National Education in 2024, is a new curriculum model. This model aims to integrate individual cognitive, affective, and social development with virtue, values, and academic achievement. The purpose of this study is to examine teachers’ views on the implementation process of CTEM and to reveal its reflections in practice. The research was conducted using the qualitative case study method; 39 teachers from different provinces of Turkey during the 2024–2025 academic year spring semester were selected through maximum variation sampling. Data were collected through a semi-structured interview form and analyzed using content analysis. The findings indicate that CTEM is considered the strongest by teachers in the themes of student-centered learning, multidimensional student development, and skill-based teaching. In contrast, it is seen to require improvement in themes such as academic achievement, self-expression skills, inclusive education and social interaction skills, holistic education, strengthening educational infrastructure, preparation for life skills, individual learning differences, and discovery and curiosity motivation. In terms of equality and justice, despite CTEM’s strong goals, teachers emphasize possible challenges due to resource shortages, infrastructural inadequacies, and regional disparities. Furthermore, teachers expect the most significant changes in professional development and guidance and counseling roles. However, the prominence of the theme "increase in official documentation and reporting workload" shows teachers’ concerns about additional bureaucratic tasks. The most frequently suggested solution for ensuring the applicability of CTEM is strengthening professional development programs for teachers.